CHATBOTS IN E-COMMERCE: A STUDY OF GEN Z CUSTOMER EXPERIENCE AND ENGAGEMENT – FRIEND OR FOE? - Christania Armagita Julia Tamara; Willem J. F. Alfa Tumbuan; Emilia Margareth Gunawan (Universitas Sam Ratulangi, 2023)
With chatbots becoming more common in e-commerce, concerns have arisen about how Gen Z users perceive these virtual assistants. This study intends to investigate how Gen Z perceives chatbots in general and how they impact customer engagement and the e-commerce experience. Using semi-structured online interviews, a qualitative study methodology was used to collect information from 15 Generation Z individuals who had interacted with chatbots on e-commerce platforms in Manado City, Indonesia. In-depth knowledge of the perspectives, experiences, and complex actions of Gen Z customers around chatbots in e-commerce is made possible by the use of thematic analysis, which identifies patterns and themes in the data that has been collected. According to research, chatbots are often viewed as allies by Gen Z customers as they offer convenience, quick replies, and around-the-clock accessibility. However, there are problems with their ability to understand difficult questions and provide customized solutions. The study's conclusions emphasize the significance of elements like information accuracy, personalization, and interface usability in determining how Gen Z clients interact and interact with chatbots. By identifying areas for improvement and adjusting chatbot interactions to meet the expectations of Gen Z clients, e-commerce organizations may optimize customer care initiatives and improve customer experiences. The recommendations include enhancing chatbot functionality and design, personalizing interactions to users' interests, encouraging openness and trust, providing smooth human handoffs, and implementing multi-channel support. Keywords: chatbots, e-commerce, customer experience, customer engagement